EVALUASI DIKLAT MODEL KIRKPATRICK PELATIHAN PEMBENTUKAN PENGENDALI EKOSISTEM HUTAN KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Gamin Gamin (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
The education and training for the establishment of Forest Ecosystem Controllers that has been carried out in 2019 is not yet known for its efficiency, effectiveness, and impact on alumni performance in the field. This paper aims to describe the effectiveness of the training implementation and the impact of the training on the alumni's performance. Quantitative approach involving a population of 34 alumni is used for this study. Kirkpatrick's evaluation model was applied to determine the reaction, outcome, behavior, and impact of the training. Performance is assessed using a 360-degree method involving alumni, immediate supervisors, and alumni colleagues. The reaction to the training was rated